Pelatihan Penilaian Autentik bagi Guru-Guru SD Muhammadiyah 3 Parakan, Pamulang, Tangerang Selatan, Banten - Imam Safi'i; Wini Tarmini; Sobri Sobri (Universitas Mathla'ul Anwar Banten, 2021)
AUTHENTIC ASSESSMENT TRAINING FOR TEACHERS OF SD MUHAMMADIYAH 3 PARAKAN, PAMULANG, TANGERANG SELATAN, BANTEN. Authentic assessment is a form of assessment that is highly emphasized in the 2013 Curriculum because it has a significant impact on student learning outcomes in the realm of attitudes, skills, and knowledge. This training activity aims to improve the professional competence of teachers of SD Muhammadiyah 3 Parakan, Pamulang, Tangerang Selatan, Banten in making authentic assessment instrumen s. This training is conducted in three sessions, namely exploration, elaboration, and confirmation sessions. The exploration session begins with the submission of various questions via google form related to the training participants' understanding of authentic assessment. In the elaboration session, the training participants were given an explanation of the various characteristics of authentic assessment along with examples of authentic assessment models that can be applied in evaluating learning outcomes. At the confirmation stage, the trainees are asked to make authentic assessment instruments related to the subjects they are teaching. This training is able to improve the professional competence of the teachers of SD Muhammadiyah 3 Parakan, Pamulang, South Tangerang in making authentic assessment instruments. The initial average ability of the teachers was 63. After participating in the training activities, the average ability of the teachers increased to 81.